2010
DOI: 10.1111/j.1741-1130.2010.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Special Education into Postschool Services for Young Adults With Intellectual Disability: Irish Parents' Experience

Abstract: The authors conducted a study to address gaps in the literature regarding parents' experiences of the transition of their child from special education to postschool mainstream services. Specifically, this study sought to explore the nature, factors, and psychological impact of their child's transition to post‐school services. To achieve these aims, a qualitative, grounded theory approach was employed in which semi‐structured interviews were conducted with a small sample of parents of children with mild intelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 28 publications
(50 reference statements)
3
33
0
3
Order By: Relevance
“…Research has shown that effective transition planning must include efforts to make students feel heard and valued in planning meetings [33,46]. Suggested strategies include allowing peer advocates, friends and/or mentors as active participants [33] and ensuring student involvement occurs at an early stage [42,47]. Additionally, in order to uphold the UN Convention on the Rights for Persons with Disabilities, all transition related planning materials should be provided in an accessible manner for individuals with intellectual disability [48].…”
Section: System Levelmentioning
confidence: 97%
“…Research has shown that effective transition planning must include efforts to make students feel heard and valued in planning meetings [33,46]. Suggested strategies include allowing peer advocates, friends and/or mentors as active participants [33] and ensuring student involvement occurs at an early stage [42,47]. Additionally, in order to uphold the UN Convention on the Rights for Persons with Disabilities, all transition related planning materials should be provided in an accessible manner for individuals with intellectual disability [48].…”
Section: System Levelmentioning
confidence: 97%
“…As families navigate this transition, adult siblings may assume greater caregiving and supervising responsibilities of their brother or sister with IDD (Hall & Rossetti, 2017). Amidst changing caregiver roles, families may also feel challenged by discontinuity in services and barriers to education, employment and community living and participation (Gillan & Coughlan, 2010;Leonard et al, 2016). The balance between independence and protection may be especially difficult to achieve as emerging adults with IDD explore environments beyond the structure of school and the safety of home (Almack et al, 2009).…”
mentioning
confidence: 99%
“…; Davies & Beamish ; Neece et al . ; Power ; Gillan & Coughlan ). The transition period out of the educational system is no exception, as parents lose indirect respite and educational services (Power ), and face significant life adjustments (Davies & Beamish ).…”
Section: Discussionmentioning
confidence: 99%
“…() reported the feelings of fulfilment, pride and personal growth that parents with chronic demands experienced. Successful transitions that increase the youth's confidence and enjoyment can be rewarding for parents (Gillan & Coughlan ). While strategies to facilitate successful transitions can be implemented (McDonnell & Hardman ), overwhelmingly, this transition is viewed as difficult and stressful (Baxter et al .…”
Section: Introductionmentioning
confidence: 99%